(untitled) (Research in Agriculture Livestock and Fisheries, 2021)
The experiment was carried out to investigate the effect of rhizobium inoculum and phosphorus fertilization on nodulation, growth, and yield of soyabean cv. Binasoybean-2 at the area of Chamberkella, East Subarnachar Upazila, Noakhali, Bangladesh, from mid-January to first week of May 2018. Four levels of Rhizobium inoculation viz: 0, 25, 50 and 75 g kg-1 and four levels of phosphorus viz: 0, 18, 36 and 54 kg P ha-1 were applied. The experiment was laid out in a randomized complete block design (RCBD) with three replications. The effect of interaction of different combinations of Rhizobium inoculation and phosphorus rates showed regular trend, although their effects on some of studied growth, and yield parameters were insignificant but most of the growth and yield parameters were significant. Among sixteen treatment combinations the highest grain yield (2.217 t ha-1) was obtained from the treatment combination of 50 g kg-1 Rhizobium inoculation and 36 kg ha-1 phosphorus which was statistically identical with 50 g kg-1 Rhizobium inoculation with 18 kg ha-1, the lowest yield (1.367 t ha-1) was recorded with control treatment. Res. Agric., Livest. Fish.8(1): 9-17, April 2021